The Influence Of An Interactive Learning Model Game Based Learning Using The Wordwall Application On The Geographic Literacy Of Class X Students In MA AN-Nur Gio Parigi Moutong District - Nispa; Hasan, Haslita Rahmawati; Nurvita, Nurvita; Novarita, Amalia (Journal of Geography Science and Education, 2025)
The aim of this research is to determine the influence of the interactive game-based learning model using the Wordwall application on the technological literacy of class X students in Geography Learning at MA An-Nur Gio. This research uses quantitative research methods with a Quasi Experimental research type. Data collection techniques include observation, tests and documentation to determine the effect of the interactive game based learning model using the Wordwall application on students' Geography literacy. Through a series of data analysis tests which include pretest and posttest, as well as implementing various analysis tests using the SPSS IBM 25 application. Based on the results of the n-gain test results in the experimental class it was 60.15% while for the control class it was 17.66%, so it can It was concluded that the n-gain in the experimental class had increased compared to the control class. Based on the hypothesis test, there is a difference in scores between the posttest class and the experimental class, the control class reached 69.16, the posttest reached 83.46. This proves that the Game Based Learning interactive learning model using the Wordwall application has an influence on increasing students' Geography literacy at MA AN-Nur Gio Parigi Moutong Regency.